Influences of environmental variables on the weight-length relationship of the shrimp Xiphopenaeus kroyeri: Do variations occur along time? - BENEDITTO,ANA PAULA M. DI (2022)
Abstract This study analyzes the influences of environmental variables on the weight-length relationship of the penaeid shrimp Xiphopenaeus kroyeri during nine consecutive years (2005 to 2013) in northern Rio de Janeiro State. The main questions raised are: i) Does species relative growth vary along time? and ii) How are the environmental variables sea surface temperature, salinity, chlorophyll-a and/or organic matter related to the relative growth? For males, the long-term mean of the allometric coefficient stayed <3 (immature: 2.49; mature: 2.91), whereas for females they were >3 (immature: 3.08; mature: 3.10). The sine-consine models highlighted the wave T period in which the allometric coefficient values complete one cycle of increase-decrease: 4.72 years and 14.72 years for immatures female and male, respectively; and 9.08 years and 9.98 years for matures male and females, respectively. The relative growth behavior varies in a predictable time scale; however, none of the environmental variables strongly supported the variation. Changes in the relative growth behavior are probably drive by intrinsic mechanisms to maintain the population locally.